Influência da complexidade estrutural sobre a reprodução da ictiofauna: o caso das árvores submersas em reservatórios - Daga, Patrícia Salete (2012)
The heterogeneity of the habitat assumes that structurally complex habitats can increase the diversity of species. In aquatic environments these complex habitats also play an important role in the biological diversity, in the interspecific relations and in the system s productivity. Studies have shown that several fish species seek sites with structured habitats for their reproduction. This study intends to evaluate the influence of the structural complexity provided by submerged trees on the ichthyplankton in the influence area of two reservoirs located in Parana River basin, demonstrating the importance of such sites known as paliteiros. The samples were carried out in places with and without the presence of submerged trees from October 2009 to March 2010. For these samples, we used plankton nets with mesh size of 0.5mm equipped with a measurer to obtain the volume of filtered water. The process was realized with continuous drag, using two plankton nets. We determined the abundance of larvae, number of species, Shannon s diversity index and the indicator taxons for each environment analyzed. To determine if there were any significant spatial variation we applied the t-test. The composition of the ichthyoplanktonic assemblage in the different environments was summarized based on a correspondence analysis (CA). During the study 122,099 individuals were captured, belonging to 22 species, six orders, 19 families. Within this sample, 78.84% are individuals captured in environments without any structure, whereas 21.16% are individuals captured in structured environments. In both places the most abundant species were Hypophthalmus edentatus and Plagioscion squamosissimus. The places with submerged trees presented the highest values in richness and abundance of species, which indicates that spawning may have been occurring in headwaters located in areas with submerged vegetation, and that eggs, as well as larvae, are passively carried by water flows to development areas, located at lower areas in the reservoir. This study indicates that areas with submerged vegetation play a very important part in fish reproduction in the sampled reservoirs and, therefore, their preservation may be indispensable for the future presence of many fish species in these environments.